Evidence and uptake routes for Zinc oxide nanoparticles through the gastrointestinal barrier in Xenopus laevis. Issue 7 (November 2014) - Bacchetta, Renato; Moschini, Elisa; Santo, Nadia; Fascio, Umberto; Del Giacco, Luca; Freddi, Stefano; Camatini, Marina; Mantecca, Paride
Abstract The developmental toxicity of nanostructured materials, as well as their impact on the biological barriers, represents a crucial aspect to be assessed in a nanosafety policy framework. Nanosized metal oxides have been demonstrated to affect Xenopus laevis embryonic development, with nZnO specifically targeting the digestive system. To study the mechanisms of the nZnO-induced intestinal lesions, we tested two different nominally sized ZnO nanoparticles (NPs) at effective concentrations. Advanced microscopy techniques and molecular marker analyses were applied in order to describe the NP-epithelial cell interactions and the mechanisms driving NP toxicity and translocation through the intestinal barrier. We attributed the toxicity to NP-induced cell oxidative damage, the small-sized NPs being the more effective. This outcome is sustained by a marked increase in anti-oxidant genes' expression and high lipid peroxidation level in the enterocytes, where disarrangement of the cytoskeleton and cell junctions' integrity were evidenced. These events led to diffuse necrotic changes in the intestinal barrier, and trans- and paracellular NP permeation through the mucosa. The uptake routes, leading NPs to cross the intestinal barrier and reach secondary target tissues, have been documented. nZnOs embryotoxicity was confirmed to be crucially mediated by the NPs' reactivity rather than their dissolved ions. The ZnO NPs' ability to overwhelm the intestinal barrier must be taken into high consideration for a future design of safer ZnO NPs.